Research on the method of responsibility division of transboundary water pollution. Issue 1 (February 2021) - Yanqiong, Ma; Manchun, Liang; Qilin, Zhao; Gang, Xu; Mei, Li; Xia, Zhang; Chunyan, Chen
Abstract: With the rapid development of China's economy and society, there has been a serious crisis in the field of water environment safety. Due to the mobility of water and the spatial distribution of water in the basin and other reasons, cross-border water pollution has become a major issue of general concern to the state and the whole society. In this paper, the scope of responsibility of pollutants is generated using the one-dimensional steady-state water quality dynamics based on the basic data of the target area, the corresponding basic data of water quality, water quantity, administrative scope and responsible person so on, so as to realize the comprehensive responsibility division of water quality of cross-border water bodies. The pollutant attenuation coefficient was used to calculate the pollution concentration of pollutants from the initial section of the upstream of the responsibility jurisdiction to the section of the river section at the end of the jurisdiction, which can avoid the calculation error caused by the concentration changes of the pollutants under the comprehensive effects of hydrology, hydraulics, chemistry, physics, geography, biochemistry, climate, location and meteorology in the process of transportation, and improve the accuracy of pollution liability definition of each administrative area.